Spurious Inference in Reduced-Rank Asset-Pricing Models - Gospodinov, Nikolay; Kan, Raymond; Robotti, Cesare (Econometrica, 2017)
We study some seemingly anomalous results that arise in possibly misspeciﬁed, reduced-rank linear asset-pricing models estimated by the continuously updated generalized method of moments. When a spurious factor (that is, a factor that is uncorrelated with the returns on the test assets) is present, the test for correct model speciﬁcation has asymptotic power that is equal to the nominal size. In other words, applied researchers will erroneously conclude that the model is correctly speciﬁed even when the degree of misspeciﬁcation is arbitrarily large.The rejection probability of the test for overidentifying restrictions typically decreases further in underidentiﬁed models where the dimension of the null space is larger than 1.